Kepemilikan Manajerial dan Praktik Penghindaran Pajak: Studi pada Perusahaan Manufaktur terdaftar di BEI Periode Tahun 2015-2017 - Nanik Niandari; Rachmawaty Hanny Yustrianthe; Evi Grediani (Owner : Riset dan Jurnal Akuntansi, 2020)
This study test the effect of managerial ownership on propensity of tax avoidance behaviour. Data used in this study were obtained from Indonesian stock exchange database and company's annual report. The author uses regression analysis with unbalanced panel data types from a sample of 144 manufacturing companies covering years period of 2015 to 2017. Propensity of tax avoidance as a dependent variable is measured by effective tax rate (ETR). The independent variable is managerial ownership which is determined by 2 (two) types of measurements. First measurement use a percentage form, and second measurement use a dummy based on the level of managerial ownership. The control variables used include return on assets (ROA), company size and leverage. We find that managerial ownership has a positive effect on propensity of tax avoidance. Another finding in this study is that the effect of managerial ownership on propensity of tax avoidance occurred at managerial ownership levels of less than 20%. The results of this study are expected to contribute the literature study of managerial ownership towards propensity of tax avoidance.